2004
DOI: 10.1086/382493
|View full text |Cite
|
Sign up to set email alerts
|

Congenital Disorder of Glycosylation Type Ik (CDG-Ik): A Defect of Mannosyltransferase I

Abstract: This study describes the discovery of a new inherited disorder of glycosylation named "CDG-Ik." CDG-Ik (congenital disorder of glycoslyation type Ik) is based on a defect of human mannosyltransferase I (MT-I [MIM 605907]), an enzyme necessary for the elongation of dolichol-linked chitobiose during N-glycan biosynthesis. Mutations in semiconserved regions in the corresponding gene, HMT-1 (yeast homologue, Alg1), in two patients caused drastically reduced enzyme activity, leading to a severe disease with death i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
47
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
7
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 77 publications
(50 citation statements)
references
References 18 publications
(14 reference statements)
0
47
0
Order By: Relevance
“…This indicates that TMEM165 deficiency affects the glycosylation of various proteins and that the changes are not restricted to transferrin. The faint pattern of the second sample can be explained by the patient's nephrotic syndrome since it has been observed that the consequent protein loss can account for faint patterns in IEF (Kranz et al 2004).…”
Section: Discussionmentioning
confidence: 99%
“…This indicates that TMEM165 deficiency affects the glycosylation of various proteins and that the changes are not restricted to transferrin. The faint pattern of the second sample can be explained by the patient's nephrotic syndrome since it has been observed that the consequent protein loss can account for faint patterns in IEF (Kranz et al 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Compared with other CDG types, the phenotype in ALG1-CDG is very severe, with rapid development of microcephaly, seizures refractory to treatment, progressive stupor, and death in early infancy (Kranz et al 2004). The hypoglycosylation of liver-derived serum glycoproteins is more profound than in other types of CDG-I.…”
Section: Discussionmentioning
confidence: 96%
“…We previously identified the HMT-1 gene, orthologous to the yeast ALG1 (31), which encodes human MT-I (32). Since then, it has been demonstrated by several groups that dysfunction of HMT-1 results in CDG-Ik (33)(34)(35)(36). Of seven substitutional mutations reported to drastically decrease MT-I activity, S150R and G145D mutations are notable, because Ser 150 and Gly 145 residues of human MT-I are neither conserved nor located within a conserved domain.…”
Section: E-6 Perspectivesmentioning
confidence: 99%